2012
DOI: 10.1530/rep-11-0461
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy development from day 28 to 42 of gestation in postpartum Holstein cows that were either milked (lactating) or not milked (not lactating) after calving

Abstract: The objective was to determine if lactation affects fetal and placental development from day 28 to 42 of gestation. Bos taurus Holstein cows were assigned to one of the two treatments immediately after parturition (lactating (nZ23) or nonlactating (dried off immediately after calving; nZ20)). Cows were inseminated at w60 days postpartum with semen from a single ejaculate. Pregnant cows were slaughtered at 1 of 3 days of gestation (day 28, 35, or 42) and tissues were collected. The interval to first inseminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
5
36
0
1
Order By: Relevance
“…Insulin may have mediated stimulatory effects of glucose on postpartum IGF1 through its capacity to recouple the somatotropic axis. The magnitude of the IGF1 increase in response to glucose that was observed (10 to 15 ng/ml) approximated the magnitude of IGF1 difference reported elsewhere for cows that have or have not commenced oestrous cycles (Beam and Butler, 1998) or postpartum pregnant v. non-pregnant cows (Taylor et al, 2004;Green et al, 2012). The infusion studies demonstrated that a single molecule (glucose) could rapidly reverse the metabolic profile that typifies early lactation.…”
Section: Glucose: a Central Molecule Involved In Lactation And Reprodsupporting
confidence: 71%
See 2 more Smart Citations
“…Insulin may have mediated stimulatory effects of glucose on postpartum IGF1 through its capacity to recouple the somatotropic axis. The magnitude of the IGF1 increase in response to glucose that was observed (10 to 15 ng/ml) approximated the magnitude of IGF1 difference reported elsewhere for cows that have or have not commenced oestrous cycles (Beam and Butler, 1998) or postpartum pregnant v. non-pregnant cows (Taylor et al, 2004;Green et al, 2012). The infusion studies demonstrated that a single molecule (glucose) could rapidly reverse the metabolic profile that typifies early lactation.…”
Section: Glucose: a Central Molecule Involved In Lactation And Reprodsupporting
confidence: 71%
“…Later postpartum (30 to 60 days postpartum) there was no relationship between plasma concentrations of glucose and pregnancy. Green et al (2012) and Garverick et al (2013) examined association between postpartum blood glucose and pregnancy at first AI. In separate studies performed in Ireland (Cummins et al, 2012;Moore et al, 2014), blood concentrations of glucose were examined in dairy cows with similar genetic merit for milk production but with good or poor genetic merit for fertility (Fert + or Fert − , respectively).…”
Section: Glucose: a Central Molecule Involved In Lactation And Reprodmentioning
confidence: 99%
See 1 more Smart Citation
“…High-yielding cows show a higher ability to mobilize energy reserves during the early lactation period [8,9]. This may result in metabolic changes, leading to a decrease in reproductive parameters due to functional changes of the reproductive system [10], which translate into lower conception rate and increased likelihood of pregnancy loss [11].…”
Section: Introductionmentioning
confidence: 99%
“…Garverick et al (2013) reported an increase in circulating glucose concentrations in postpartum dairy cows that were pregnant at first AI compared with cows that failed to conceive at first AI. Similarly, Green et al (2012) reported decreased plasma glucose concentration during the first 30 d postpartum in dairy cows that did not conceive at first AI when compared with pregnant dairy cows. However, Mulliniks et al (2013) reported elevated serum glucose and reduced insulin concentrations with late conception cows compared with early conception cows.…”
Section: Resultsmentioning
confidence: 79%